Familial Urethral Stricture, Five Adult Patients Overview - Hosseini, Jalil; Kazemzadeh Azad, Babak; Aliakbari, Fereshteh; Tayyebi azar, Ali; Hosseini, Mohammad Ali (Urology Journal, 2019)
Congenital stricture, specifically with manifestation in adulthood is extremely a rare cause of urethral stricture and is not associated with known etiologies. It was first described by Cobb et al., and to our knowledge only 5 families were reported in English literatures to have familial urethral stricture. We report two families with urethral stricture including five male patients referred to our tertiary reconstructive urology department during 1994 to 2017. The age and severity of symptoms at presentation are variable; as are the surgical interventions required. There are no phylogenetic, familiar or racial relationship between the two families described.